PEMBUATAN PETA SITUASI SKALA 1:500 DUSUN PURWOSASONO DAN DUSUN BABADAN DESA BELUK KECAMATAN BAYAT KABUPATEN KLATEN PROPINSI JAWA TENGAH - , ANNISA RACHMA IZZATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final project describes about (PKL) on 14-26 April 2014 the measurement and mapping of land to produce a spatial data information from the Earth's surface. Spatial data includes spot height data and planimetric measurements obtained from the surface of the earth that will be presented in the form of map with specific scale. The activity is orientation, put some pole, horizontal measurement control framework and vertical control framework, the measurement of planimetric detail and spot height, and also digital mapping with specific software. The final result is a situation that presents a map of spatial data on the earth's surface area designated areas in the Purwosasono village and Babadan village, Beluk village, Bayat sub-district, Klaten district in Central Java province in 1:500 scale projection system is UTM (Universal Transverse Mercator)